2018
DOI: 10.3126/bdg.v20i0.20723
|View full text |Cite
|
Sign up to set email alerts
|

Geological Study of Chatara–Barahakshetra Section, Sunsari-Udayapur District, Eastern Nepal

Abstract: Geological mapping was carried out in the Chatara–Barahakshetra area of east Nepal. The Siwalik of the Chatara–Barahakshetra area is divided into the Lower Siwalik and the Middle Siwalik. Each unit is further subdivided into lower and upper members. The Central Churia Thrust is overturned in the study area. Highly deformed Siwalik contain several outcrop-scale as well as a large-scale folds. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 49-58

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, the correlation of Siwaliks litho units based on the local stratigraphic name is quite complicated. However, the well-adopted classification (three-fold i.e., the Lower, Middle and Upper Siwaliks), where litho units are classified based on the grain size (Piligram, 1913;Auden 1935;Ulak, 2004;Ulak, 2009;Adhikari et al, 2018). The present study also adopted this classification (Table 2) and correlated the other section of the Siwalik Group.…”
Section: Correlationmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the correlation of Siwaliks litho units based on the local stratigraphic name is quite complicated. However, the well-adopted classification (three-fold i.e., the Lower, Middle and Upper Siwaliks), where litho units are classified based on the grain size (Piligram, 1913;Auden 1935;Ulak, 2004;Ulak, 2009;Adhikari et al, 2018). The present study also adopted this classification (Table 2) and correlated the other section of the Siwalik Group.…”
Section: Correlationmentioning
confidence: 97%
“…Different researchers studied the Siwalik Group along the Muskar Khola section (Quade et al, 1995;Shrestha and Sharma, 1996;Robinson et al, 2001;Ojha et al, 2009;DMG, 2011;Chirouze et al, 2012), but none of these studies described the lithostratigraphy in detail. Therefore, this study is focused on a detailed lithological description and a stratigraphic classification of Siwalik succession based on classical threefold classification, which was previously used in the study of the different Siwalik section (Pilgrim, 1908, Hagan, 1951Shrestha and Sharma, 1996;Ulak, 2004;Ulak, 2009;Adhikari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Shrestha (2017) correlated the Lesser Himalayan section with that of central Nepal as the Lukwa Formation with the Dhading Dolomite, the Chiuribas Formation with the Nourpul Formation and the Mulghat Formation with the Dadagaon Phyllite. Later on, Adhikari et al (2018) published the geological map of the Siwalik of the Chatara-Barahakshetra section, in which the authors stated the zone as a highly deformed area as it contains several folded structures. Further, the rock sequence near the CCT suggested it as an overturned structure.…”
Section: Early Investigationsmentioning
confidence: 99%
“…The study area comprises of the rocks of the lower and the upper member of Lower Siwalik Formation. The classification is based on the basis of proportion of mudstone and sandstone Adhikari et al (2018). The lower member comprises of purple, greenish grey to grey mudstone and shale alternating with 5 to 30 cm thick, fine to medium grained, bluish grey, calcareous to non-calcareous, sandstone, which transitionally passes to the upper member of the formation.…”
Section: Siwaliksmentioning
confidence: 99%
“…All the previous study indicated that the landslide bearing area is structurally weak zone and bears multiple thrust zones in close succession of horizontal distance suggesting that the area has suffered through multiple stages of deformation. Present study is focused on delineation of geological state of focused area in which the classification names adopted as presented by Dhital (2015) and Adhikari et al (2018), and to find out geotechnical cause of the Nishane landslide that has been obstructing the traffic of the Koshi Highway.…”
Section: Introductionmentioning
confidence: 99%